(E)-7-Ethylidene-lithocholic Acid (7-ELCA) Is a Potent Dual Farnesoid X Receptor (FXR) Antagonist and GPBAR1 Agonist Inhibiting FXR-Induced Gene Expression in Hepatocytes and Stimulating Glucagon-like Peptide-1 Secretion From Enteroendocrine Cells - Stefela, Alzbeta; Kaspar, Miroslav; Drastik, Martin; Kronenberger, Thales; Micuda, Stanislav; Dracinsky, Martin; Klepetarova, Blanka; Kudova, Eva; Pavek, Petr (Frontiers in Pharmacology, 2021)
Bile acids (BAs) are key signaling steroidal molecules that regulate glucose, lipid, and energy homeostasis via interactions with the farnesoid X receptor (FXR) and G-protein bile acid receptor 1 (GPBAR1). Extensive medicinal chemistry modifications of the BA scaffold led to the discovery of potent selective or dual FXR and GPBAR1 agonists. Herein, we discovered 7-ethylidene-lithocholic acid (7-ELCA) as a novel combined FXR antagonist /GPBAR1 agonist (IC50 = 15 μM / EC50 = 26 nM) with no off-target activation in a library of 7-alkyl substituted derivatives of BAs. 7-ELCA significantly suppressed the effect of the FXR agonist obeticholic acid in BSEP and SHP regulation in human hepatocytes. Importantly, 7-ELCA significantly stimulated the production of glucagon-like peptide-1 (GLP-1), an incretin with insulinotropic effect in postprandial glucose utilization, in intestinal enteroendocrine cells. We can suggest that 7-ELCA may be a prospective approach to the treatment of type II diabetes as the dual modulation of GPBAR1 and FXR has been supposed to be effective in the synergistic regulation of glucose homeostasis in the intestine.